Determination of Material Constants of Magneto-optical Crystals Using the Faraday Effect under Magneto-mechanical Resonance Conditions - Linchevskyi, I.V.; Petrishchev, O.N. (Ukrainian Journal of Physics, 2022)
It is theoretically substantiated and experimentally proven by the example of yttrium garnet ferrite that, in ferro- and ferrimagnetic crystals subjected to a constant bias and an additional alternating magnetic fields, magnetostriction phenomena result in additional changes of the variable magnetization component in a vicinity of the alternating-field frequencies close to the resonance frequencies of natural magneto-mechanical oscillations of the crystal. It is shown that these changes can be revealed by measuring the variable component of a turn of the polarization plane of light that passes through the crystal. A technique for the determination of the material constants of a crystal is proposed.